Genetic, epigenetic and metabolite variation in peripheral European Yew (Taxus baccata L.) populations at an unexplored part of the species natural distribution - Eleftheria Dalmaris; Evangelia Avramidou; Eirini Sarrou; Aliki Xanthopoulou; Salvatore Multari; Stefan Martens; Filippos A. Aravanopoulos (PLoS ONE, 2026)
Taxanes form effective anticancer agents, which are found in the leaves and bark of the yew tree ( Taxus L.). Paclitaxel (Taxol®) and related taxanes are widely used in cancer therapy. Due to the high demand of taxanes, there is strong pharmaceutical interest in evaluating unexplored population diversity as a potential genetic and biochemical resource. Three peripheral Greek Taxus baccata L . populations (Mt Cholomon, Mt Olympus and Mt Vourinos) were investigated to assess genetic (microsatellite markers), epigenetic (methylation sensitive amplified markers) and chemodiversity (targeted LC-MS/MS analysis of five major taxanes) variation. Taxane concentration varied significantly among populations and seasons. The dominant compound in needles was 10-deacetylbacatin III (DAB), ranging from 267.8 (Mt Vourinos) to 517.6 (Mt Olympus) mg kg -1 dw. Substantial genetic diversity (AR = 5.00; He = 0.537) and significant population differentiation (Fst = 0.153) were detected, while epigenetic analyses showed moderate haploid epigenetic diversity (H epi = 0.051) and comparable levels of DNA methylation across populations. Multivariate analyses indicated clear population structuring in genetic and metabolomic profiles, whereas epigenetic variation was less strongly structured. Together, these results demonstrate pronounced spatial and seasonal variation in taxane production, alongside considerable genetic differentiation, and sufficient levels of total methylation, suggesting a potential capacity for responses to future climatic change. Our findings highlight peripheral Greek populations as valuable genetic resources for conservation and breeding aimed at sustainable taxane production.